Transformasi Layanan Publik melalui E-Goverment: Evaluasi layanan aplikasi Identitas Kependudukan Digital di Dinas Pencatatan Sipil Kabupaten Tuban - Sinta Adia Pramesti; Esa Septian; Musta`ana (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The implementation of e-Government through application at the Digital Identity (Disdukcapil) of Tuban Regency aims to enhance the efficiency and accessibility of civil registration services for the community. However, the adoption of this application still faces various challenges, including low levels of digital literacy among the public, infrastructure limitations, and technical obstacles. This study aims to evaluate the effectiveness of the IKD application in improving the quality of public services and to identify the barriers faced by the community in using this application. The research method employed is a qualitative approach, utilizing interviews and observations with users of the IKD application and service officials. The findings indicate that although the IKD application has significant potential in supporting e-Government, there are substantial barriers to its adoption, particularly in rural areas with limited internet access. Furthermore, the IKD application is seen as needing enhancement in terms of features and data security to improve user experience and trust. Based on these findings, it is recommended that the government strengthen its outreach efforts, improve application features, and ensure user data security so that the IKD application can be optimized as an inclusive and efficient public service solution.